POTENSI SEDIAAN HAND SANITIZER EKSTRAK AIR DAUN BIDARA ARAB (Ziziphus Spina-christi L.) SEBAGAI ANTIBAKTERI - Trie Yuni Elfasyari; Suci Santana; Shinta Sari Dewi; Zulfisa (Journal Pharma Saintika, 2025)
Arabian sidr leaves (Ziziphus spina-christi L.) contain secondary metabolites such as alkaloids, flavonoids, saponins, tannins, and phenolics, which have the potential to act as antibacterial agents. This study was designed to evaluate the antibacterial activity of a hand sanitizer formulation containing aqueous extract of Ziziphus spina-christi leaves (EADBA). The stability of the hand sanitizer was assessed through organoleptic tests, homogeneity, pH, viscosity, hedonic evaluation, and antibacterial activity against Staphylococcus aureus using the phenol coefficient method. The antibacterial test was conducted by observing turbidity in a bacterial suspension after the addition of the sample at minutes 5, 10, and 15. Results indicated that the EADBA hand sanitizer remained physically stable during four weeks of storage at both cold (4±2°C) and room temperature (±25°C). Formulations F1 and F2 demonstrated antibacterial activity equivalent to that of phenol, as evidenced by a phenol coefficient value of one.